The holistic management concept in rearing Nguni cattle: a way out for sustainable agriculture and minimizing rural poverty? - Arko-Achemfuor, Akwasi; Dzansi, Dennis Yao (Environmental Economics, 2015)
This study explores how the holistic management concept is being applied by the Tiger Kloof Educational Institution to ensure sustainable agriculture in rural South Africa. Holistic management in sustainable development provides benefits in three areas of development, which are the environment, economic and social. Before the advocacy for what is now referred to as the triple bottom line principle, businesses would only consider the economic aspect of doing business, which has proven to be unstainable in most instances. The Tiger Kloof Educational Institution is applying the holistic veld management in practical farmer training on Nguni cattle to promote and maintain biodiversity, improve water and mineral cycles and rear cattle that are purely grass-fed thus leading to low cost production. There are health and poverty reduction benefits that are noticeable in the surrounding towns and villages. The study uses the case study design to ascertain how the holistic management principle that is being applied at the institution is ensuring sustainability. The findings indicate that holistic management, as applied at the institution, meets the triple bottom line criteria that can be replicated in other rural communities in South Africa and elsewhere to ensure sustainable development.
Published Article
Keywords: diodiv; development; holistic management; Nguni; sustainability